Pressure-induced hydride superconductors above 200 K - Xiaohua Zhang (AIP Publishing LLC, 2021)
Although it was proposed many years ago that compressed hydrogen should be a high-temperature superconductor, the goal of room-temperature superconductivity has so far remained out of reach. However, the successful synthesis of the theoretically predicted hydrides H3S and LaH10 with high superconducting transition temperatures TC provides clear guidance for achieving this goal. The existence of these superconducting hydrides also confirms the utility of theoretical predictions in finding high-TC superconductors. To date, numerous hydrides have been studied theoretically or experimentally, especially binary hydrides. Interestingly, some of them exhibit superconductivity above 200 K. To gain insight into these high-TC hydrides (>200 K) and facilitate further research, we summarize their crystal structures, bonding features, and electronic properties, as well as their superconducting mechanism. Based on hydrogen structural motifs, covalent H3S with isolated hydrogen and several clathrate superhydrides (LaH10, YH9, and CaH6) are highlighted. Other predicted hydrides with various H-cages and two-dimensional H motifs are also discussed. Finally, we present a systematic discussion of the common features, current problems, and future challenges of these high-TC hydrides.